Potencial de remineralização do cálcio e fosfato: revisão de literatura e estudo laboratorial - Hirata, Edo [UNESP] (Universidade Estadual Paulista (Unesp), 2006)
A descoberta do efeito preventivo do flúor transformou esse material, ao longo do século XX, no principal agente responsável pela queda de prevalência de cárie, em vários países. Existem fortes evidências de que produtos fluoretados são os principais responsáveis pelo declínio observado na prevalência da cárie, e também pelo aumento na incidência de fluorose dental. Se pudéssemos diminuir sua concentração, sem perder efeito cariostático, sua margem de segurança seria maior ainda. O cálcio e fosfato fazem parte, juntamente com o flúor, do processo de equilíbrio mineral entre esmalte e saliva. A busca dos efeitos anticárie do cálcio e fosfato datam da década de 1960, quando alimentos foram enriquecidos com estes elementos. Experimentos com compostos contendo cálcio e/ou fosfato vêm sendo estudados, com o objetivo de compreendermos melhor os efeitos do cálcio e fosfato e a possibilidade do aumento de seu uso em produtos fluoretados. Na primeira parte do trabalho, realizamos uma revisão com tópicos relevantes para a compreensão de seu potencial anticariogênico. Na segunda parte, realizamos experimento in vitro para avaliar o potencial de remineralização de um dentifrício de baixa concentração de flúor suplementado com cálcio e fosfato. Pode-se concluir que a suplementação de dentifrícios fluoretados, com cálcio e fosfato, é mais um recurso na prevenção da cárie.

The use of fluoride was largely responsible for the drop in caries prevalence over the last few years, however, a great part of the population still suffers from its consequences and sequelae. The search for an ally to combat caries has impelled research in several directions, including the use of antimicrobial agents, sugar substitutes, food supplements and remineralizing agents. The effects of food supplements (bread, cereals, jellies, chewing gums, milk, honey) and other products, such as fluoridated dentifrices, with combinations of calcium and phosphates have been studied with the object of reducing caries incidence in animals and humans. With the object of having a better understanding of the effects of calcium and phosphate and the possibility of increasing their use in fluoridated products, a review was made of relevant topics to understand their anticariogenic potential. It was found that the use of calcium and phosphate, together with fluoride, forms part of the mineral balance process: enamel X saliva and/or biofilm; theoretical considerations indicate that calcium and phosphate, in adequate amounts in the biofilm, may diminish enamel dissolution; experiments with calcium- and/or phosphate-containing compounds have been studying supersaturation of these elements in saliva and biofilm, with the object of increasing enamel protection. It may be concluded that calcium and phosphate are of great importance in tooth enamel demineralization and remineralization events, and the possibility of applying the preventive action of these two elements, has made it possible to develop new products, both food and for use in dentistry, providing more treatment and caries prevention options.
Keywords: Calcio; Fosfatos; Esmalte dentário; Fluor; Caries dentarias - Prevenção; Dentifrícios; Dentifrices; Calcium; Phosphates; Dental enamel; Fluorine; Dental caries